Dimension of taxpayers' perceived quality towards the behavioral intention in using e-filing of the inland revenue board of Malaysia (IRB) / Awang Sebli Awang Bojeng...[et.al] - Awang Bojeng, Awang Sebli; Zainal Abidin, Siti Nadia; Mohd Ibrahim, Soffian (2019)
Tax as a source of revenue is a key element for a country's growth and development. THe introduction of e-Filing system by IRB has helped to increase the collection of taxes since its inception in 2006.